GrabFood - The Impact of Electronic Coupons on Consumer’s Purchasing Power - Wei, Crystal Chee Jia; Xuan, Ding; Ziru, Cui; Jingru, Cui; Kushwah, Vedant Singh (AIBPM Publisher, 2023)
With the development of Internet technology and the impact of COVID-19, many people are switching from offline platforms to online platforms. Electronic coupons issued by merchants are also growing in popularity. The issue of electronic vouchers makes it more convenient for consumers to shop and provides consumers with more choices. This paper aims to analyze the influence of electronic coupons on consumers' purchasing power. Data were collected 162 GrabFood users’ questionnaires via Google Forms. This study examined whether perceived ease of use, trust, convenience, coupon proneness, social influence, price, and attitude affect consumers’ purchasing power. The findings indicate a positive correlation between purchasing power and factors such as perceived ease of use, trust, price, and attitude. Notably, price exerts the most significant influence on consumers’ purchasing power, followed by attitude. The study reveals that perceived ease of use and social influence play roles in shaping consumers’ purchase intentions through their attitudes. In the context of Grab food, enhancing the ease of use and increasing promotional activities on its social platforms can enhance consumer attitudes towards e-coupons.